2015
DOI: 10.1021/acs.energyfuels.5b00589
|View full text |Cite
|
Sign up to set email alerts
|

Semidetailed Kinetic Model for Gasoline Surrogate Fuel Interactions with the Ignition Enhancer 2-Ethylhexyl Nitrate

Abstract: A semidetailed chemical kinetic model has been developed describing the interaction of gasoline surrogate fuels with the ignition enhancer 2-ethylhexyl nitrate (2EHN). The model, which consists of 788 reactions among 157 species, has been checked for validity using ignition delay data obtained in a shock tube for the fuel n-heptane and rapid compression machine for primary and toluene reference fuels. The validation showed that the model can predict the reactivity trends in the measured data including differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This could lead to variation in the ignition enhancing capabilities of the additive. To the best of our knowledge, no study has reported such behaviors, but simulations performed by a reviewer of this article, using Andrae’s model, showed that 2-EHN addition into a PRF90 leads to a similar behavior (under the conditions defined in Figure ).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…This could lead to variation in the ignition enhancing capabilities of the additive. To the best of our knowledge, no study has reported such behaviors, but simulations performed by a reviewer of this article, using Andrae’s model, showed that 2-EHN addition into a PRF90 leads to a similar behavior (under the conditions defined in Figure ).…”
Section: Resultsmentioning
confidence: 81%
“…They also quantify the effect of two additives on the ignition delay of a PRF90: di- tert -butyl-peroxide (DTBP) and 2-ethylhexyl nitrate (EHN). These two additives are well-known ignition enhancers of conventional fuels , because of their ability to generate free radicals at low temperatures, through a relatively easy initial bond fission. These free radicals promote the hydrocarbon reactivity and contribute to decreasing the ignition delay time of the hydrocarbon fuel/air mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…Both the n-C7H16 and n-C16H34 kinetic models are sourced from the POLIMI library [22,23]. A 2-EHN kinetic model has been added to these models to account for the influence of 2-EHN on the chemical kinetics and thermodynamics which control the fuel oxidation, with kinetic and thermodynamic parameters adopted from the work of Andrae [24]. Sub-mechanisms for NOx and low molecular weight alkyl nitrate species are pre-existing in the POLIMI databases.…”
Section: Chemical Kinetic Modelingmentioning
confidence: 99%
“…Reaction chemistry simulations of fuels additized with EHN are generally performed with the two-step chemical-kinetic mechanism shown in Figure 1, [18][19][20] and only few more comprehensive models of EHN decomposition can be found in the literature. 21 Hartmann et al 18 experimentally studied the autoignition and combustion characteristics of n-heptane doped with EHN in both a shock tube and burner apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…They simulated the experiments using the two-reaction model of Figure 1 to model EHN unimolecular thermal decomposition, concluding that the increased reactivity of the fuel was mainly due to the 3-heptyl radical activity. Andrae 19 studied the impact of EHN additive on the autoignition characteristics of multiple gasoline-like surrogates by numerical simulations, in which EHN decomposition was modeled by a single reaction that forms NO 2 , CH 2 O, and 3-heptyl radical. Goldsborough et al 20 utilized a rapid compression machine testing facility to perform experimental studies of two different gasoline surrogates additized with EHN.…”
Section: Introductionmentioning
confidence: 99%